Comparison of wind measurements in the troposphere and mesosphere by VHF/MF radars and in-situ techniques - N. Engler; W. Singer; R. Latteck; B. Strelnikov (Annales Geophysicae, 2008)
Radar wind observations at frequencies between 1.98 and 53.5 MHz obtained at polar latitudes were compared to in-situ wind measurements by radiosondes at tropospheric altitudes and to winds from falling spheres at mesospheric altitudes. Comparisons are shown for several campaigns of radiosonde and falling sphere observations. The radar wind directions agree well to the radiosonde and falling sphere observations and are highly correlated. The winds estimated from radar measurements are less than the radiosonde data by about 15% for spaced antenna observations and by about 10% for the Doppler beam swinging experiment. At mesospheric altitudes the spaced antenna winds obtained from the wide-beam Andenes MF radar are underestimated in the order of 35% and winds from the narrow-beam Saura MF radar are underestimated by about 20% compared to falling sphere winds at altitudes between 70 and 80 km. Furthermore, the relation between wind measurements using narrow-beam and wide-beam antenna arrangements for the MF radars is discussed and VHF radar observations are compared to the wide-beam MF radar.